A novel reliability prediction with input transients for an LLC converter - Darla, Ramesh B.; Annamalai, Chitra (Frontiers in Energy Research, 2022)
Reliability is an essential factor for the power electronic product manufacturers and operators in order to achieve the functional requirements and quality. The conventional approach uses generic data to predict the failure prediction in useful lifetime. However, the various faults and transients have an impact on the converter failure rate prediction in the remaining useful lifetime. Experiments are conducted to get the actual stress values at input transient and fault conditions, which helps to predict the failure rate. Therefore, this paper presents a procedure to estimate the reliability of the power electronic-based converters using experimental data from the component level to the system level at different mission profiles with field transient operating conditions. Effect of reliability with other stress factors like temperature stress, environmental stress, electrical voltage, current, and power stress on failure rates are also presented. Failure rate and Mean Time Between Failures (MTBF) have been calculated for an LLC converter using the experimental data. The proposed reliability model can be used in the design phase to have an optimal design, planning, and operation of a power electronic converter in the field